Referee Bias in Professional Football: Favoritism Toward Successful Teams in Potential Penalty Situations - Erikstad, Martin Kjeøen; Johansen, Bjørn Tore (Frontiers in Sports and Active Living, 2020)
Past studies have indicated that multiple factors may influence sport referees' decisions, such as pressure from spectators and athletes' reputation. Grounded in the social impact theory framework, this study examined whether Norwegian Premier League (NPL) referees are biased by a team's success when awarding penalties. Using video footage (similar to video assistant referees), an expert panel (EP) of four NPL referees evaluated all potential penalty situations (N = 43) involving either of two successful teams during an entire NPL season. Fifty-five potential penalty situations from matches without successful teams were also rated. Overall, the match referees identified 73.3% (22 of 30) of the EP-identified penalties during matches without successful teams. Successful teams were awarded 110% (11 of 10) of the EP-identified penalties, while their opponents were awarded 12.5% (1 of 8). Chi square statistic revealed that successful teams were more likely to receive an incorrect penalty compared with their opponents, and less likely to be denied a penalty they should have been awarded. These findings indicate that referees' decisions may be unintentionally biased by a team's success, extending our knowledge about how football referees may be influenced by social forces.